Reaction and free-energy pathways of hydrogen activation on partially promoted metal edge of CoMoS and NiMoS: A DFT and thermodynamics study - Chanchai Sattayanon (2018)
© 2017 Elsevier B.V. Understanding of molecular hydrogen (H 2 ) activation mechanism on MoS 2 -based catalysts is crucial for enhancement of catalytic hydrotreating processes. In this work, H 2 activation reaction pathways including adsorption, dissociation, and diffusion phases on metal edge of partially Co-promoted MoS 2 (CoMoS) and partially Ni-promoted MoS 2 (NiMoS) catalysts under hydrotreating conditions have been investigated using density functional theory and thermodynamic calculations. Here, investigation of H 2 adsorption on CoMoS and NiMoS catalysts shows that H 2 molecule prefers to adsorb on the promoter site rather than the sulfur site, while the H 2 molecule adsorbs firmly on CoMoS but substantially weaker on NiMoS. H 2 dissociation is the rate-determining step for both CoMoS and NiMoS catalysts and the activation energy (E a ) of rate-determining step for both catalysts is identical (E a  = 0.79 eV). However, thermodynamic result indicates that CoMoS is more reactive toward H 2 activation than NiMoS (free energy of activation (ΔG ‡ ) at 575 K = 0.65 and 1.14 eV for CoMoS and NiMoS, respectively). In terms of diffusion, hydrogen atom migrates relatively easy (E a   <  0.55 eV) on both CoMoS and NiMoS surfaces. Partial charge analysis reveals that both heterolytic and homolytic H 2 dissociation characteristics are observed on CoMoS and NiMoS depending on the reaction site. In addition, dissociated hydrogen atoms are more stable in terms of thiol group (S[sbnd]H) on CoMoS while metal-hydrogen pairs (Mo[sbnd] H and Ni[sbnd]H) are more stable on NiMoS.